A DEA study to evaluate the relative efficiency and investigate the district reorganization of the Taiwan Power Company. - Feng-Yu Lo (IEEE Transactions on power systems)
In this study, data envelopment analysis (DEA) models were applied to evaluate the relative efficiencies of twenty-two electricity distribution districts of the Taiwan Power Company (TPC) in Taiwan, ROC. The empirical study showed that the TPC districts have good overall efficiency. We found that eleven districts were inefficient. Most of the inefficient districts suffer from scale inefficiency to a greater degree than technical inefficiency. We suggested the specific improvement directions for the corresponding inefficient districts. This study also investigated district reorganization to increase the efficiency. The proposed district reorganization alternatives have higher efficiency scores than the current one